TEXTILE AND HABERDASHERY PRODUCTS: ASSORTMENT, PURPOSE AND QUALITY INDICATORS - Олійник, Галина Миколаївна; Рубанка, Алла Іванівна; Мамченко, Яна Олександрівна; Остапенко, Наталія Валентинівна; Кузьменко, Володимир Володимирович (Art and Design, 2024)
Purpose: to study the range of textile and haberdashery products. To summarise and systematise information about their varieties according to various features, to describe the areas of application. To determine their quality indicators for the military garments manufacture. The information-research and visual-analytical approaches in combination with general scientific methods of typological systematisation and comparative analysis of textile haberdashery existing types for the foreign and domestic production military garments manufacture were applied. The article analyses the modern textile haberdashery products range, presents a list of leading world and domestic manufacturers. The most common types of textile goods are singled out and systematised, the materials used for their manufacture are characterised. The quality indicators for the military products manufacture are listed. The packaging and labelling types are described. The textile and haberdashery products types are structured by purpose, the characteristic structural and compositional features by size, material of manufacture, etc. are revealed. Their quality indicators for the military products manufacture are determined. Practical significance of the results obtained is to allocate the main types of textile and haberdashery products and determine their main functions. The characteristic features according to the purpose, raw material composition, and manufacturing method are revealed. The results can be used in the further products development for this purpose. Their quality indicators for the military products manufacture are determined.